Anti-osmotic and antioxidant activities of gigantol from Dendrobium aurantiacum var. denneanum against cataractogenesis in galactosemic rats. (22nd August 2015) - Fang, Hua; Hu, Xiaohong; Wang, Meiling; Wan, Wencheng; Yang, Qiaohong; Sun, Xiaosheng; Gu, Qiong; Gao, Xinxin; Wang, Zhengtao; Gu, Lianquan; Oliver Chen, C.-Y.; Wei, Xiaoyong
Abstract: Ethnopharmacological relevance: Dendrobium aurantiacum var. denneanumis widespread in southern China, locally known as "Shihu", "Huangcao" or "Fengdou", has long been used in traditional Chinese medicine for antipyretic, immunomodulatory, anti-aging effects and eye benefiting. Aim of this study: To investigate the effects of gigantol extracted from the stem of D. aurantiacum var. denneanum on the formation of galactose-induced cataractogenesis and the potential mechanisms underlying these effects. Materials and methods: Cataract lens models were induced byd -galactose both in vitro and in vivo . The transparency of the rat lenses in vitro and in vivo was observed with an anatomical microscope and a slit lamp microscope. The differential protein and action targets of gigantol were determined and compared among the control group, model group, and gigantol group using two-dimensional electrophoresis and mass spectrometry (MS). Enzyme kinetics was used to show the ability of gigantol to respress aldose reductase (AR) and inducible nitric oxide synthase (iNOS). Quantitative real-time PCR (RT-qPCR). was used to detect repression of the expression of AR and iNOS genes. Molecular docking and dynamic simulation were used to predict the interaction points and combination patterns between gigantol, AR, and iNOS. Results: Gigantol was found to prevent galactose-induced damage to the rat lenses both in vitro and in vivo, to delay lens turbidity, and to keep the lenses transparent. Differential proteomes, MS, and RT-qPCR showed AR and iNOS to be the target proteins of gigantol. Gigantol reduced the galactose-induced AR and iNOS mRNA expression by 51.2% and 60.9%, respectively. The IC50 of gigantol for inhibition of AR and iNOS activities were 65.67 μg/mL and 8.768 μg/mL, respectively. Gigantol–AR binding sites were Trp111, His110, Tyr48, and Trp20, and gigantol–iNOS binding sites were Ile195 and Gln257. The main forms of interaction were hydrophobic forces, hydrogen bonds, and van der Waals forces. Conclusion: Gigantol extracted from D. aurantiacum var. denneanum was found to inhibit galactose-induced formation of cataracts through repression of the gene expression and activity of AR and iNOS. Graphical abstract: